Effect of Ni loading on SBA-15 synthesized from palm oil fuel ash waste for hydrogen production via CH4 dry reforming - Nornasuha, Abdullah; Nurul Aini, Razali; C. C., Chong; H. A., Razak; Setiabudi, H. D.; S. Y., Chin; A. A., Jalil (Elsevier, 2019)
The successful synthesis of SBA-15 using silica source extracted from palm oil fuel ash (POFA) was proven with the presence of mesostructure characteristics as evidenced by low angle XRD, N2 adsorption-desorption isotherms and TEM. Different amounts of Ni were loaded on the synthesized SBA-15(POFA) using the impregnation method at 80 °C. The influence of Ni loading over the Ni/SBA-15(POFA) physiochemical properties and CO2 reforming of CH4 (CRM) were investigated in a stainless steel fixed-bed reactor at 800 °C and atmospheric pressure with 1:1 CO2:CH4 volumetric feed composition. An increment in Ni loading on SBA-15(POFA) from 1 to 5 wt% decreased the BET surface area and crystallinity of catalyst as proven by N2 adsorption–desorption and XRD analysis. The catalytic performance of CRM followed the sequence of 3 wt% > 5 wt% > 2 wt% > 1 wt% -Ni/SBA-15(POFA). This result was owing to the even distribution of Ni and good Ni–O–Si interaction of 3 wt% Ni/SBA-15(POFA) as proved by TEM, FTIR and XPS. Lowest H2/CO ratio and catalyst activity and stability of 1 wt% Ni/SBA-15(POFA) were due to the weaker Ni–O–Si interaction and small amount of basic sites that favor the reverse water gas shift (RWGS) reaction and carbon formation. The recent finding indicates that a quantity as small as 3 wt% Ni loaded onto SBA-15(POFA) could elicit outstanding catalytic performance in CRM, which was comparable with 10 wt% Ni loading catalysts reported in literature.